2014
DOI: 10.1051/0004-6361/201423795
|View full text |Cite
|
Sign up to set email alerts
|

Observed spectral energy distribution of the thermal emission from the dayside of WASP-46b

Abstract: Aims. We aim to construct a spectral energy distribution (SED) for the emission from the dayside atmosphere of the hot Jupiter WASP-46b and to investigate its energy budget. Methods. We observed a secondary eclipse of WASP-46b simultaneously in the g r i z JHK bands using the GROND instrument on the MPG/ESO 2.2 m telescope. Eclipse depths of the acquired light curves were derived to infer the brightness temperatures at multibands that cover the SED peak. Results. We report the first detection of the thermal em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…For WASP-46b, we measure an eclipse depth of 0.26 +0.05 −0.03 %, and e cos ω = 0.004 +0.004 −0.004 , as measured from two full eclipse observations. The Ks band eclipse has previously been measured by Chen et al (2014c), with a reported depth of 0.253 +0.063 −0.060 %, consistent with our measurement to better than 1σ. Chen et al (2014c) also measured the J and H band eclipses using GROND on the ESO 2.2m.…”
Section: Resultssupporting
confidence: 92%
“…For WASP-46b, we measure an eclipse depth of 0.26 +0.05 −0.03 %, and e cos ω = 0.004 +0.004 −0.004 , as measured from two full eclipse observations. The Ks band eclipse has previously been measured by Chen et al (2014c), with a reported depth of 0.253 +0.063 −0.060 %, consistent with our measurement to better than 1σ. Chen et al (2014c) also measured the J and H band eclipses using GROND on the ESO 2.2m.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, the WASP light curve shows a photometric modulation, which allowed the measurement of the rotation period of the star, and a gyrochronological age of the system of 1.4 Gyr. By observing the secondary eclipse of the planet, Chen et al (2014b) detected the emission from the day-side atmosphere finding brightness temperatures consistent with a low heat redistribution efficiency.…”
Section: Wasp-46mentioning
confidence: 99%
“…The limited results from ground-based occultation observations in the optical and near-ultraviolet include similar non-detections (e.g. Chen et al 2014;Hooton et al 2018), but also disagreeing results that are challenging to interpret (a full discussion is contained in Hooton et al 2019). Precise occultation observations of a greater number of hot Jupiters at multiple wavelengths are required to further understand the atmospheric processes shaping the reflective properties of these extreme planets.…”
Section: Introductionmentioning
confidence: 99%